Role of Drosophila -adaptin in presynaptic vesicle recycling. - Gonzalez-Gaitan, M.; Jackle, H. (Cell, 1997)
Rapid flow of information in the nervous system involves presynaptic vesicle recycling by clathrin-mediated endocytosis, an event triggered by the alpha-adaptin-containing AP2 complex. We identified a Drosophila alpha-adaptin expressed in the garland cells, imaginal discs, and the CNS. Here we show its role in presynaptic vesicle recycling. In presynaptic terminals, alpha-adaptin defines a network-like membrane structure to which the GTPase dynamin is recruited. alpha-adaptin is necessary for the formation of clathrin-coated pits and participates in the dynamin-dependent release of coated vesicles from the membrane surface. Our results suggest an alpha-adaptin-dependent control of the vesicle cycle that maintains the balance between the amount of vesicle- and surface-associated membranes.